Diversity in new flagellum tip attachment in bloodstream form African trypanosomes. Issue 5 (14th September 2022) - Smithson, Laura; Ihuoma Akazue, Pearl; Findlater, Lucy; Gwira, Theresa Manful; Vaughan, Sue; Sunter, Jack D.
Abstract: The closely related parasites Trypanosoma brucei, T. congolense, and T. vivax cause neglected tropical diseases collectively known as African Trypanosomiasis. A characteristic feature of bloodstream form T. brucei is the flagellum that is laterally attached to the side of the cell body. During the cell cycle, the new flagellum is formed alongside the old flagellum, with the new flagellum tip embedded within a mobile transmembrane junction called the groove. The molecular composition of the groove is currently unknown, which limits the analysis of this junction and assessment of its conservation in related trypanosomatids. Here, we identified 13 proteins that localize to the flagellar groove through a small‐scale tagging screen. Functional analysis of a subset of these proteins by RNAi and gene deletion revealed three proteins, FCP4/TbKin15, FCP7, and FAZ45, that are involved in new flagellum tip attachment to the groove. Despite possessing orthologues of all 13 groove proteins, T. congolense and T. vivax did not assemble a canonical groove around the new flagellum tip according to 3D electron microscopy. This diversity in new flagellum tip attachment points to the rapid evolution of membrane‐cytoskeleton structures that can occur without large changes in gene complement and likely reflects the niche specialization of each species. Abstract : Using 3D‐electron microscopy, we have found that the flagellar groove represents a specific adaptation of Trypanosoma brucei, with this structure absent in Trypanosoma congolense and Trypanosoma vivax . Furthermore, through an endogenous tagging screen, we have successfully identified 13 proteins that localise to the Trypanosoma brucei flagellar groove. Several of these proteins are involved in new flagellum tip attachment to the groove and cytokinesis.